When the Stomach Pain Is Literally “In Your Head” - D. Jakubauskas; M. Sarafinaitė; R. Mameniškienė (Neurologijos seminarai)
Abdominal epilepsy (AE) is an extremely rare condition, classified as temporal lobe epilepsy, and is usually a diagnosis of exclusion. Temporal lobe epilepsy often has no clear cause, although it may be associated with diseases such as temporal lobe sclerosis, dysembryoplastic neuroepithelial tumours, and other benign tumours, as well as arterio-venous malformations, gliomas, defects in neuronal migration, or lesions of the cortex caused by encephalitis. AE is more common in children but has been reported in adults. AEs are characterised by recurrent and unexplained gastrointestinal symptoms such as seizure pain, nausea, bloating and diarrhoea, which improve with antiepileptic treatment. Given the vague nature of these symptoms, patients are at high risk of misdiagnosis. An electroencephalogram and neuroimaging of the brain are needed to confirm the diagnosis.